Outdoor cooking prevalence in developing countries and its implication for clean cooking policies - Jörg Langbein; Jörg Peters; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
More than 3 billion people use wood fuels for their daily cooking needs, with detrimental health implications related to smoke emissions. Global initiatives to disseminate clean cooking stoves emphasize technologies that are either expensive, such as electricity and gasifier stoves, or for which supply chains hardly reach rural areas, such as LPG. This emphasis neglects that many households in the developing world cook outdoors. Our calculations demonstrate that for such households, already the use of less expensive biomass cooking stoves can substantially reduce smoke exposure. The costeffectiveness of clean cooking policies can thus be improved by taking cooking location and ventilation into account.
Keywords: Q53; I12; O13; 330; air pollution; health behavior; energy access